# -*- coding: utf-8 -*- from benedict.dicts import KeypathDict import unittest class KeypathDictTestCase(unittest.TestCase): # def test_list_as_key(self): # keys = ['a', 'b', 'c'] # d = {} # d[keys] = 1 # print(d) # print(d[keys]) def test_fromkeys(self): k = [ 'a', 'a.b', 'a.b.c', 'a.b.d', 'a.b.e', 'x', 'x.y', 'x.z', ] b = KeypathDict.fromkeys(k) r = { 'x': { 'y': None, 'z': None, }, 'a': { 'b': { 'c': None, 'd': None, 'e': None, }, }, } self.assertEqual(b, r) # self.assertEqual(type(b), benedict) def test_fromkeys_with_value(self): k = [ 'a', 'a.b', 'a.b.c', 'a.b.d', 'a.b.e', 'x', 'x.y', 'x.z', ] b = KeypathDict.fromkeys(k, True) r = { 'x': { 'y': True, 'z': True, }, 'a': { 'b': { 'c': True, 'd': True, 'e': True, }, }, } self.assertEqual(b, r) # self.assertEqual(type(b), benedict) def test_get_with_1_valid_key(self): d = { 'a': 1, 1: 1 } b = KeypathDict(d) self.assertEqual(b.get('a', 2), 1) self.assertEqual(b.get(1, 2), 1) def test_get_with_1_invalid_key(self): d = { 'a': 1, } b = KeypathDict(d) self.assertEqual(b.get('b', 2), 2) def test_get_with_1_not_str_key(self): d = { None: None, False: False, 0: 0, } b = KeypathDict(d) self.assertEqual(b.get(None, 1), None) self.assertEqual(b.get(False, True), False) self.assertEqual(b.get(True, True), True) self.assertEqual(b.get(0, 1), 0) def test_get_with_keys_list(self): d = { 'a': { 'b': { 'c': 1, 'd': 2, }, }, } b = KeypathDict(d) self.assertEqual(b.get(['a.b.c']), 1) self.assertEqual(b.get(['a.b', 'c']), 1) self.assertEqual(b.get(['a', 'b.c']), 1) self.assertEqual(b.get(['a', 'b', 'c']), 1) self.assertEqual(b.get(['a', 'b', 'd']), 2) self.assertEqual(b.get(['a', 'b', 'e']), None) def test_getitem_with_1_valid_key(self): d = { 'a': 1, } b = KeypathDict(d) self.assertEqual(b['a'], 1) def test_getitem_with_1_invalid_key(self): d = { 'a': 1, } b = KeypathDict(d) with self.assertRaises(KeyError): val = b['b'] print(val) def test_getitem_with_1_not_str_key(self): d = { None: None, False: False, # 0: 0, } b = KeypathDict(d) self.assertEqual(b[None], None) self.assertEqual(b[False], False) with self.assertRaises(KeyError): val = b[True] print(val) self.assertEqual(b[0], 0) def test_get_with_2_valid_keys(self): d = { 'a': { 'b': 1 } } b = KeypathDict(d) self.assertEqual(b.get('a.b', 2), 1) def test_get_with_2_invalid_keys(self): d = { 'a': { 'b': 1 } } b = KeypathDict(d) self.assertEqual(b.get('b.a', 2), 2) def test_getitem_with_2_valid_keys(self): d = { 'a': { 'b': 1 } } b = KeypathDict(d) self.assertEqual(b['a.b'], 1) def test_getitem_with_2_invalid_keys(self): d = { 'a': { 'b': 1 } } b = KeypathDict(d) with self.assertRaises(KeyError): val = b['b.a'] print(val) def test_get_with_3_valid_keys(self): d = { 'a': { 'b': { 'c': 1 } } } b = KeypathDict(d) self.assertEqual(b.get('a.b.c', 2), 1) def test_get_with_3_invalid_keys(self): d = { 'a': { 'b': { 'c': 1 } } } b = KeypathDict(d) self.assertEqual(b.get('c.b.a', 2), 2) def test_getitem_with_3_valid_keys(self): d = { 'a': { 'b': { 'c': 1 } } } b = KeypathDict(d) self.assertEqual(b['a.b.c'], 1) def test_getitem_with_3_invalid_keys(self): d = { 'a': { 'b': { 'c': 1 } } } b = KeypathDict(d) with self.assertRaises(KeyError): val = b['c.b.a'] print(val) # def test_get_item_with_keys_list(self): # d = { # 'a': { # 'b': { # 'c': 1, # 'd': 2, # }, # }, # } # b = KeypathDict(d) # self.assertEqual(b['a.b.c'], 1) # self.assertEqual(b['a.b', 'c'], 1) # self.assertEqual(b.get(['a', 'b.c']), 1) # self.assertEqual(b.get(['a', 'b', 'c']), 1) # self.assertEqual(b.get(['a', 'b', 'd']), 2) # self.assertEqual(b.get(['a', 'b', 'e']), None) def test_has_with_1_key(self): d = { 'a': 0, 'b': None, 'c': {}, } b = KeypathDict(d) self.assertTrue('a' in b) self.assertTrue('b' in b) self.assertTrue('c' in b) self.assertFalse('d' in b) def test_has_with_2_keys(self): d = { 'a': { 'a': 0, 'b': None, 'c': {}, }, } b = KeypathDict(d) self.assertTrue('a.a' in b) self.assertTrue('a.b' in b) self.assertTrue('a.c' in b) self.assertFalse('a.d' in b) self.assertFalse('b' in b) self.assertFalse('b.a' in b) def test_has_with_3_keys(self): d = { 'a': { 'b': { 'c': 0, 'd': None, 'e': {}, }, }, } b = KeypathDict(d) self.assertTrue('a.b.c' in b) self.assertTrue('a.b.d' in b) self.assertTrue('a.b.e' in b) self.assertFalse('a.b.f' in b) self.assertFalse('b.f' in b) self.assertFalse('f' in b) def test_keypaths(self): d = { 'x': { 'y': True, 'z': False, }, 'a': { 'b': { 'c': 0, 'd': None, 'e': {}, }, }, } b = KeypathDict(d) r = [ 'a', 'a.b', 'a.b.c', 'a.b.d', 'a.b.e', 'x', 'x.y', 'x.z', ] self.assertEqual(b.keypaths(), r) def test_set_override_existing_item(self): d = {} b = KeypathDict(d) b.set('a.b.c', 1) r = { 'a': { 'b': { 'c': 1 } } } b.set('a.b.c', 2) r = { 'a': { 'b': { 'c': 2 } } } self.assertEqual(b, r) b.set('a.b.c.d', 3) r = { 'a': { 'b': { 'c': { 'd': 3 } } } } self.assertEqual(b, r) def test_setitem_override_existing_item(self): d = {} b = KeypathDict(d) b['a.b.c'] = 1 r = { 'a': { 'b': { 'c': 1 } } } b['a.b.c'] = 2 r = { 'a': { 'b': { 'c': 2 } } } self.assertEqual(b, r) b['a.b.c.d'] = 3 r = { 'a': { 'b': { 'c': { 'd': 3 } } } } self.assertEqual(b, r) def test_delitem_with_1_valid_key(self): d = { 'a': 1, } b = KeypathDict(d) del b['a'] with self.assertRaises(KeyError): del b['a'] self.assertEqual(b.get('a'), None) def test_delitem_with_1_invalid_key(self): d = { 'a': 1, } b = KeypathDict(d) with self.assertRaises(KeyError): del b['b'] self.assertEqual(b.get('b'), None) def test_delitem_with_2_valid_keys(self): d = { 'a': { 'b': 1, } } b = KeypathDict(d) del b['a.b'] with self.assertRaises(KeyError): del b['a.b'] self.assertEqual(b.get('a'), {}) del b['a'] with self.assertRaises(KeyError): del b['a'] self.assertEqual(b.get('a'), None) def test_delitem_with_2_invalid_keys(self): d = { 'a': { 'b': 1, } } b = KeypathDict(d) with self.assertRaises(KeyError): del b['a.c'] self.assertEqual(b.get('a'), { 'b': 1 }) def test_delitem_with_3_valid_keys(self): d = { 'a': { 'b': { 'c': 1, 'd': 2, }, } } b = KeypathDict(d) del b['a.b.c'] with self.assertRaises(KeyError): del b['a.b.c'] self.assertEqual(b.get('a.b'), { 'd':2 }) del b['a.b.d'] with self.assertRaises(KeyError): del b['a.b.d'] self.assertEqual(b.get('a.b'), {}) del b['a.b'] with self.assertRaises(KeyError): del b['a.b'] self.assertEqual(b.get('a.b'), None) def test_delitem_with_3_invalid_keys(self): d = { 'a': { 'b': { 'c': 1, 'd': 2, }, } } b = KeypathDict(d) with self.assertRaises(KeyError): del b['a.b.c.d'] self.assertEqual(b.get('a.b.c'), 1) def test_pop_with_1_valid_key(self): d = { 'a': 1, } b = KeypathDict(d) val = b.pop('a') self.assertEqual(val, 1) def test_pop_with_1_invalid_key(self): d = { 'a': 1, } b = KeypathDict(d) with self.assertRaises(KeyError): val = b.pop('b') val = b.pop('b', False) self.assertFalse(val) def test_pop_with_2_valid_keys(self): d = { 'a': { 'b': 1, } } b = KeypathDict(d) val = b.pop('a.b') with self.assertRaises(KeyError): val = b.pop('a.b') self.assertEqual(val, 1) val = b.pop('a') with self.assertRaises(KeyError): val = b.pop('a') self.assertEqual(val, {}) def test_pop_with_2_invalid_keys(self): d = { 'a': { 'b': 1, } } b = KeypathDict(d) val = b.pop('a.c', 2) self.assertEqual(val, 2) with self.assertRaises(KeyError): val = b.pop('a.c') self.assertEqual(b.get('a'), { 'b': 1 }) val = b.pop('x.y', 1) self.assertEqual(val, 1) with self.assertRaises(KeyError): val = b.pop('x.y') def test_setdefault_with_1_key(self): d = { 'a': None, 'b': 0, 'c': 1, } b = KeypathDict(d) b.setdefault('a', 2) b.setdefault('b', 2) b.setdefault('c', 2) b.setdefault('d', 2) self.assertEqual(b['a'], None) self.assertEqual(b['b'], 0) self.assertEqual(b['c'], 1) self.assertEqual(b['d'], 2) def test_setdefault_with_2_keys(self): d = { 'a': { 'a': None, 'b': 0, 'c': 1, }, } b = KeypathDict(d) b.setdefault('a.a', 2) b.setdefault('a.b', 2) b.setdefault('a.c', 2) b.setdefault('a.d', 2) self.assertEqual(b['a.a'], None) self.assertEqual(b['a.b'], 0) self.assertEqual(b['a.c'], 1) self.assertEqual(b['a.d'], 2) def test_setdefault_with_3_keys(self): d = { 'a': { 'b': { 'a': None, 'b': 0, 'c': 1, }, }, } b = KeypathDict(d) b.setdefault('a.b.a', 2) b.setdefault('a.b.b', 2) b.setdefault('a.b.c', 2) b.setdefault('a.b.d', 2) self.assertEqual(b['a.b.a'], None) self.assertEqual(b['a.b.b'], 0) self.assertEqual(b['a.b.c'], 1) self.assertEqual(b['a.b.d'], 2) def test_cast_existing_dict_with_keys_containing_dots_for_casting(self): # TODO pass def test_cast_existing_dict_with_keys_containing_dots_for_update(self): # TODO pass